Failure to utilize functions of an electronic prescribing system and the subsequent generation of ‘technically preventable’ computerized alerts - Baysari, Melissa T (BMJ Group, 2012)
OBJECTIVES: To determine the frequency with which computerized alerts occur and the proportion triggered as a result of prescribers not utilizing e-prescribing system functions. METHODS: An audit of electronic inpatient medication charts at a teaching hospital in Sydney, Australia, was conducted to identify alerts fired, to categorize the system functions used by prescribers, and to assess if use of short-cut system functions could have prevented the alerts. RESULTS: Of the 2209 active orders reviewed, 600 (27.2%) triggered at least one alert. Therapeutic duplication alerts were the most frequent (n=572). One third of these (20.2% of all alerts) was ‘technically preventable’ and would not have fired if prescribers had used a short-cut system function to prescribe. Under-utilized system functions included the option to ‘MODIFY’ existing orders and use of the ‘AND’ function for concurrent orders. Pregnancy alerts, set for women aged between 12 and 55 years, were triggered for 43% of drugs ordered for this group. CONCLUSION: Developers of decision support systems should test the extent to which technically preventable alerts may arise when prescribers fail to use system functions as designed. Designs which aim to improve the efficiency of the prescribing process but which do not align with the cognitive processes of users may fail to achieve this desired outcome and produce unexpected consequences such as triggering unnecessary alerts and user frustration. Ongoing user training to support effective use of e-prescribing system functions and modifications to the mechanisms underlying alert generation are needed to ensure that prescribers are presented with fewer but more meaningful alerts.